Another 100 of the world's best houses. (Mulgrave, Vic. : Images Pub., 2006)
Another 100 of the worlds best houses Following the success of IMAGES' first '100 of the World's Best Houses' book, we searched the globe for another collection of amazing houses. The result of this search is 'Another 100 of the World's Best Houses'. Each house in this new volume has been selected for its unique and extraordinary qualities. The overwhelming theme is the way in which architects use their remarkable skills to relate these masterpieces to their various contexts and landscapes. Locations are as diverse as the houses themselves and include the coast of Peru, inner-city London, rugged Australian coastal sites, urban Sao Paulo, spectacular New Zealand alpine retreats and coastal hideaways, American prairies, frosty Oslo, the gorgeous West Indies, tropical Southeast Asia, suburban Lithuania, Costa Rica, and many other fascinating sites. 725 col., 90 b.andw.
Floor plans included.
Includes index.
Keywords: Architecture, Domestic -- Pictorial works; Architecture, Domestic